Developing nature tourism potency at buffer villages of Gunung Leuser National Park: case study of Bahorok Resort, Langkat Regency, North Sumatra - Pindi Patana; Tarihoran, Bill Clinton; Usanos, Nora Arriazu (Global Forest Journal, 2025)
Bahorok is a sub-district in the Gunung Leuser National Park (GLNP), LangkatRegency, North Sumatra Province. Bahorok has buffer villages directly adjacentto the national park such as Timbang Lawan Village, Batu Jongjong Village, andLau Damak Village. These three villages have many interesting tourist attractions,such as natural scenery, rivers, mountains, waterfalls, caves, and wildlife. Theprominent attractions in the villages are the beautiful landscape and wildlife. Thisstudy aims to determine the potential of natural tourism and develop a strategy fortourism in the buffer villages of GLNP, Bahorok Resort. The methods used in thisstudy are observation and interview with purposive sampling. Data was analyzedusing guidelines for developing destination and SWOT analysis. The results ofthis study show that the potential of tourism objects in buffer villages is feasibleto be developed, and increases business opportunities. The three villages arefeasible to be developed as new destinations. Tourism feasibility of the threevillages varies, in Timbang Lawan Village 72.75%, Batu Jongjong Village79.88% and Lau Damak Village 73.58%. Furthermore, they have differences indeveloping tourism strategies based on the specific internal and external factor.The progressive strategy for Timbang Lawan Village (quadrant I), a changingstrategy for Lau Damak Village (quadrant III), and a diversification strategy forBatu Jongjong Village (quadrant II). It shows how important the role of buffervillages at Bahorok Resort in developing tourism in the future.